PSYCHOLOGICAL BASIS OF EDUCATION OF SCHOOL STUDENTS IN THE SPIRIT OF SPIRITUAL PERFECTNESS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is typical of today's globalization process, in which the psychological foundations of educating young people in the spirit of spiritual perfection and its content are studied. The role of national customs, traditions and values in the education of love and loyalty to the Motherland and humanitarian qualities among young people is explained in detail.